A Study and Analysis of Covid Effected Patients - Dr. D Bujji Babu, Sk. Anjaneyulu Babu, K.Jaya Krishna, Dr. S. Suresh Kumar, Dr. S. Jafar Ali Ibrahim (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Due to COVID-19 pandemic public health emergency was created throughout the world. So, we took the base data and perform analysis on how the effect of vaccination on the human lives in terms of recovery, severity, side effects and deaths on the globe. We also analyzed the country wise vaccination to understand the scenarios in the world, because the covid virus is transforming in different countries in different ways, therefore the understanding the mutations of the virus and the use of the drug analysis also very much important for the future generations and also useful to face the future covid virus mutations